THE ROLE OF THE EMPOWERMENT OF FAMILY WELFARE AND EMPOWERMENT TEAM (PKK) IN REDUCE THE STUNTING RATE IN LITO VILLAGE PAGUYAMAN PANTAI DISTRICT, BOALEMO REGENCY - Sri Inang Akuba; Ikram Muhammad; Karlina Napu (Jurnal Ilmu Manajemen dan Bisnis, 2023)
The purpose of this study was to describe the role of the Family Welfare andEmpowerment Team (PKK) in reducing the number of stunting cases in LitoVillage, PaguyamanPantai District, Boalemo Regency.In this study, the research approach used is a qualitative approach with descriptiveresearch type. Data collection is carried out in natural settings (natural conditions),primary data sources and data collection techniques that are mostly involved inobservation as well as in-depth interviews and documentation. The data analysistechnique used is a data analysis technique by processing data using the Miles andHuberman model.The results showed that 1) the role of the Lito Village Family Welfare andEmpowerment Mobilizing Team in promotive services for stunting reduction inLito Village, PaguyamanPantai District, Boalemo Regency was running well. Therole of the Lito Village Family Empowerment and Welfare Mobilizing Team inpreventive services for stunting reduction in Lito Village, PaguyamanPantaiDistrict, Boalemo Regency is in accordance with the provisions laid down. there is.The only weakness lies in the lack of good cooperation in carrying out stuntingprevention. And 3) The role of the Lito Village Family Welfare and EmpowermentMobilization Team in curative services for stunting reduction in Lito Village,Paguyaman Pantai District, Boalemo Regency has been running conducively, thebiggest problem is the lack of budget in maximizing stunting healing for childrenand toddlers in Lito Village.